PENGARUH DISIPLIN KERJA, KOORDINASI DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PUSKESMAS SURUH KABUPATEN SEMARANG - Rhana Nuansa Bening; Edy Purwo Saputro (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research is to find out whether there is an influence between work discipline, coordination and supervision on the performance of employees at the Suruh Community Health Center, Semarang Regency. The research method used is a quantitative approach. Data collection was carried out by distributing questionnaires directly to respondents. The respondents in this study were all employees of the Semarang District Public Health Center with a total population of 76 people. The results obtained from the research show that the variables of work discipline, coordination and supervision simultaneously have a positive and significant effect on employee performance. The performance of employees at the Suruh Community Health Center, Semarang Regency.